2021
DOI: 10.3390/ijerph19010148
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Migration and Transformation of Microplastics in Inland Water Systems

Abstract: Plastic productions continue to grow, and improper management of plastic wastes has raised increasing concerns. This reflects the need to explore the microplastics in water bodies. Microplastics have been regarded as emerging pollutants in water systems. In recent years, large numbers of studies across the world were conducted to investigate the distribution, behavior and the integrated impacts of microplastics in both the marine environment and the freshwater environment. Compared with the marine environment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 96 publications
0
24
0
2
Order By: Relevance
“…While most plastic and MP studies focused on the various compartments of the marine environment, investigations carried out in freshwater bodies have expanded significantly in recent years ( Talbot and Chang, 2022 ). Freshwater bodies, such as rivers, lakes, and lagoons, display different types of hydrodynamics compared to the marine environment and may act as transport pathways for litter to reach the oceans ( Cai et al, 2021 ). For this reason, freshwater bodies play an important role in the litter dynamics across aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…While most plastic and MP studies focused on the various compartments of the marine environment, investigations carried out in freshwater bodies have expanded significantly in recent years ( Talbot and Chang, 2022 ). Freshwater bodies, such as rivers, lakes, and lagoons, display different types of hydrodynamics compared to the marine environment and may act as transport pathways for litter to reach the oceans ( Cai et al, 2021 ). For this reason, freshwater bodies play an important role in the litter dynamics across aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…It was because zone 2 was actually closed surface water, which was not directly connected to other rivers around the catchment area, that this zone noted the lower AMWI values in the pre-MCO period. Cai et al ( 2021 ) found that closed surface water systems, such as rivers from the Tibet Plateau and Indian Rivers, tended to accumulate fewer pollutants than open water systems. The in situ measurement of Fe concentration in zone 2 was averaged at 685 g/l.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, they examined the migration routes and transportation processes employed by microplastic from landfills to nearby water bodies and subterranean or freshwater. The main land-toocean routes for the transportation of microplastics are streams (Cai et al (2021). The connection of waterways was altered by profitable dam building, which decreased the flow of microplastics into the ocean.…”
Section: Related Workmentioning
confidence: 99%